Vindfällning, tillväxt och plantuppslag i en 13-årig granskärm i Medelpad - Tjernell, Tomas (2007)
The interest for alternative forest regeneration methods increased significantly during the 1990´s after 50 years dominance of the clear-cutting system (Holgén & Hånell 2000). One reason for this was that clear-cutting was being more and more questioned by different envi-ronmental organizations and because the forest sector for economical reasons wanted to find cheaper ways to regenerate forests. In the beginning of the 1990´s two shelterwood experi-ments were established in a joint effort by Svenska Cellulosa Aktiebolaget (SCA) and the Dept of Silviculture, Swedish University of Agricultural Sciences (SLU). The experiments include various forms of cutting and shelterwood densities and represent productive spruce forests in central and north Sweden (Roggsjön in the province of Medelpad and Skikkis-jöberg in the province of Västerbotten, respectively ). The experiment next to Roggsjön has been reported earlier in three MSc theses, and is also the focus of this thesis. The experiment includes two adjacent spruce stands with elements of birch and is located east of the lake Roggsjön (62, 4˚ degrees N, 216 above sea level) about 60 km west of Sundsvall. The stands are managed and administered by SCA. At the time of the shelterwood cutting, in early 1994, both stands were about 90 years old and contained approximately 300m3/ha (Andersson, 1995). The experiment was designed in randomized blocks with two blocks and four shelterwoods: 400 Dominant trees (400 H), 250 Dominant trees (250 H), 400 Co- dominant trees (400 MH), 250 Co- dominant trees (250 MH). Thirteen years later windthrow damage were extensive among the co- dominant trees, fore-most in the sparser shelterwood (250 MH), where 70 % of the trees had blown down. In the denser shelterwood (400 MH) approx. 40 % had blown down whereas the windthrow dam-ages where fairly small in the shelterwoods with dominant trees, (approx. 10 %). A strong correlation was stated between strength of cutting and redundancy. In all shelterwoods the spruce regeneration met the ...